2011
DOI: 10.1111/j.1528-1167.2011.03254.x
|View full text |Cite
|
Sign up to set email alerts
|

Insular-opercular seizures manifesting with sleep-related paroxysmal motor behaviors: A stereo-EEG study

Abstract: SUMMARYPurpose: Sleep-related complex motor seizures are a common feature of nocturnal frontal lobe epilepsy. Nevertheless, recent studies also suggest that sleeprelated hypermotor seizures can originate in the insula. The present study describes the electroclinical features of eight drug-resistant epileptic patients with insularopercular seizures manifesting with nocturnal complex motor seizures. Methods: Patients underwent a comprehensive presurgical evaluation, which included history, interictal electroence… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

8
102
0
3

Year Published

2012
2012
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 115 publications
(118 citation statements)
references
References 48 publications
8
102
0
3
Order By: Relevance
“…Such studies have helped define the clinical concept of the epileptogenic network [29,30] and enabled the characterization of the frontal and extra-frontal networks involved in sleep-related epilepsies. [31][32][33][34][35][36] S-EEG has also provided novel human data on the local pathological, paraphysiological and physiological activity of different cortical and subcortical structures during the different states of the sleep-wake cycle. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] …”
Section: A N U S C R I P Tmentioning
confidence: 99%
See 1 more Smart Citation
“…Such studies have helped define the clinical concept of the epileptogenic network [29,30] and enabled the characterization of the frontal and extra-frontal networks involved in sleep-related epilepsies. [31][32][33][34][35][36] S-EEG has also provided novel human data on the local pathological, paraphysiological and physiological activity of different cortical and subcortical structures during the different states of the sleep-wake cycle. [37][38][39][40][41][42][43][44][45][46][47][48][49][50][51][52] …”
Section: A N U S C R I P Tmentioning
confidence: 99%
“…[32,35,106] In the future, a classification according to functional and structural connectivity [105][106][107] of the insula with its surrounding regions might provide better semiologic localization.…”
Section: Sleep-related Epileptic Clinical Manifestations In Nfle Confmentioning
confidence: 99%
“…4 The evolution of epileptiform discharges either in deep brain structures or structures tangential to recording scalp electrodes is deemed to account for the lack of scalp EEG abnormalities; indeed, viscerosensitive symptoms like laryngeal and throat disturbances and breathing discomfort have been reported to characterize an insular origin of seizures and to arise in response to electrical stimulation of the anterior part of the insula. 5,6 Extra-insular spreading of epileptic discharge to frontomesial regions is instead deemed to entrain complex motor manifestations. 5 …”
Section: Discussionmentioning
confidence: 99%
“…5,6 Extra-insular spreading of epileptic discharge to frontomesial regions is instead deemed to entrain complex motor manifestations. 5 …”
Section: Discussionmentioning
confidence: 99%
“…Several works [16, 18, 19] have shown that extrafrontal resective surgery provides excellent results in these cases. …”
Section: Concept Of Nocturnal Frontal Lobe Epilepsy (Nfle)mentioning
confidence: 99%